Preparing Students for Inclusive Education Through Effective Organization of Educational Work in Specialized State Educational Institutions - Erkin Bakitovich Aydarov (Academia One Publishing, 2023)
the article talks about methods of preparing students for inclusive education through effective organization of educational work in specialized state educational institutions
Keywords: inclusive education; pedagogy; disability